Molecular characterization of heat tolerance in eggplant (Solanum melongena) lines using SSR markers - S, SANTHIYA; P, SAHA; S, TOMAR B; D, SAHA N; GHOSHAL, CHANDRIKA; LATA, SUMAN (The Indian Journal of Agricultural Sciences, 2020)
High temperature is one of the most important environmental stresses causing heavy reduction in yield of eggplant (Solanum melongena L.) in India. Therefore, development of heat tolerant eggplant variety is an important breeding objective. The present investigation was conducted to assess genetic variation among 62 eggplant lines including heat tolerant and susceptible lines in order to identify novel heat tolerant lines in changing climate in India. We employed 15 simple sequence repeat (SSR) markers to study polymorphisms among eggplant lines obtained from eggplant breeding program. The observations were analyzed using Power Marker version 3.5. The range of amplified number of bands was from 2 to 3 in each of 15 markers. The allele frequency was ranged from 0.5 to 0.7931 with an average of 2.067 alleles per locus. Among the 15 polymorphic SSR markers, 67% markers had PIC value higher than 0.3 with heterozygosity of individual loci was ranged from 0.00 to 0.1667. The marker emf01C03 had higher number of allele (3) and the marker emd03C01 had maximum PIC value and gene diversity. The NJ dendrogram obtained by 15 SSR markers divides 62 lines into 7 clusters where the cluster VII comprised of most heat tolerant lines (DBL-21, Guhala Chatua Local). The amplification pattern of heat tolerant lines also differ which implies different genetic architecture of heat tolerant lines. The research work will be very useful to combine these diverse sources of genetic variability to develop heat tolerant variety (s) in eggplant.